2018
DOI: 10.1002/bdr2.1360
|View full text |Cite
|
Sign up to set email alerts
|

CBP/p300 inhibitor C646 prevents high glucose exposure induced neuroepithelial cell proliferation

Abstract: Our data provide complementary insights for potential mechanisms of maternal diabetes induced NTDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…High glucose is a significant risk factor for NTDs. Bai et al have reported that maternal diabetes leads to an increase in H4K5/K8/K12/K16 acetylation levels, and that the CBP selective inhibitor, C646, could efficiently prevent an increase or emergence of histone H4 acetylation and neuroepithelial cell proliferation (Bai et al, 2018). Furthermore, a deletion in the neuronal Nap1l2 (nucleosome assembly protein 1-like 2) gene in mice leads to an increase in acetylated histone H3K9/14 at the Cdkn1c transcription site and causes NTDs (Attia, Rachez, De Pauw, Avner, & Rogner, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…High glucose is a significant risk factor for NTDs. Bai et al have reported that maternal diabetes leads to an increase in H4K5/K8/K12/K16 acetylation levels, and that the CBP selective inhibitor, C646, could efficiently prevent an increase or emergence of histone H4 acetylation and neuroepithelial cell proliferation (Bai et al, 2018). Furthermore, a deletion in the neuronal Nap1l2 (nucleosome assembly protein 1-like 2) gene in mice leads to an increase in acetylated histone H3K9/14 at the Cdkn1c transcription site and causes NTDs (Attia, Rachez, De Pauw, Avner, & Rogner, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As described in our previous paper (Bai et al., 2018), diabetes was induced in 7‐ to 9‐week‐old virgin female FVB mice by two intraperitoneal injections of 100 mg/kg body weight streptozotocin (STZ; CAS18883‐66‐4, Sigma) in 100 mM sodium citrate buffer at pH 4.5 performed at an interval of 1 week. After fasting for 12 hr, 11 dams were confirmed as having diabetes when the blood glucose level exceeded 14 mM (250 mg/dl) after STZ treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Although DMSO has these defined properties for cellular differentiation, its effect on direct cardiac reprogramming has never been reported. cAMP response element-binding protein (CREB) binding protein (also called CBP or KAT3A) and adenoviral E1A binding protein p300 (also called p300 or KAT3B) are two homologues of transcriptional coactivators which play important roles in many biological processes, including proliferation [25], differentiation [26] and apoptosis [27]. Both CBP and p300 have similar protein structures, consisting of five protein interaction domains: the nuclear receptor interaction (RID) domain, kinase-inducible (KIX) domain, cysteine/histidine region (TAZ1/CH1 and TAZ2/CH2) and interferon response binding domain (IBiD).…”
Section: Introductionmentioning
confidence: 99%